Sinomenine Attenuated Capsaicin-Induced Increase in Cough Sensitivity in Guinea Pigs by Inhibiting SOX5/TRPV1 Axis and Inflammatory Response - Ma, Jian-Ling; Ji, Kun; Shi, Li-Qing; Li, Niu-Niu; Wang, Li-Yun; Dong, Shang-Juan; Zhang, Yan-Xia; Wen, Shao-Hui; Liu, Xue-Mei; Wang, Ying; Luo, Jing-Yue (Frontiers in Physiology, 2021)
Background: Chronic cough is a common complaint which affects a large number of patients worldwide. Increased cough sensitivity is a very important cause of chronic persistent cough. However, there are limited clinical diagnosis and treatment for increased cough sensitivity. Transient receptor potential vanilloid-1 (TRPVl) is a member of the transient receptor potential (TRP) family of channels which is very closely associated with respiratory diseases. However, the mechanism through which TRPV1 that influences downstream events is still poorly understood. Results: Capsaicin induced increase in cough sensitivity by upregulating the protein level of TRPV1, leading to the secretions of SP and NKA which stimulated neurogenic inflammation. However, sinomenine, a component of traditional Chinese medicine, significantly attenuated the capsaicin-induced cough by inhibiting the expression of TRPV1 in guinea pigs. In addition, capsaicin increased the expression of SOX5 which mediated the transcriptional upregulation of TRPV1. However, pretreatment with sinomenine reduced the expression of SOX5. Conclusion: These results indicate that capsaicin induced increase in cough sensitivity by activating neurogenic inflammation, while sinomenine attenuated the increase in cough sensitivity by inhibiting the expressions of SOX5 and TRPV1 in guinea pigs. This finding may provide a novel target for the treatment of aggravated cough sensitivity.